Multiscale mechanisms of green concrete regulated by silicon-to-calcium ratio: Physico-mechanical properties, hydration structure, and durability performance - Jiayuan Lou; Yiwen Liang; Wenhua Zha; Qiang Su (PLoS ONE, 2026)
To explore efficient pathways for the resource utilization of silicon-rich solid wastes in low-carbon concrete, this study proposes a synergistic regulation strategy centered on the silicon-to-calcium (Si/Ca) ratio. Three types of silicon-rich solid wastes-glass sand, glass powder, and rice husk ash-were incorporated to produce waste glass and rice husk concrete (WGRC). The effects of varying Si/Ca ratios on the workability, mechanical properties, and durability of WGRC were systematically investigated. Furthermore, the underlying mechanisms were elucidated through microstructural analysis. The results indicate that WGRC exhibits optimal overall strength within a Si/Ca ratio range of 0.46 ~ 0.58. When the Si/Ca ratio ranged from 0.52 ~ 0.58, WGRC demonstrated superior resistance to water penetration and sulfate attack, with the lowest mass loss rate (0.54% after 180 drying-wetting cycles) and the smallest ultrasonic velocity reduction (only 2.6%). At a Si/Ca ratio of 0.58, the carbonation resistance was maximized, yielding the lowest carbonation rate. In addition, the Si/Ca ratio within the C-S-H gel increased progressively with curing age, though the rate of increase slowed after 90 days. A shear damage constitutive model was developed to accurately describe the nonlinear response characteristics under varying Si/Ca ratios and shear angles, validating the coupling relationship among composition, structure, and performance. These findings provide new theoretical insights and design strategies for the synergistic utilization of multiple solid wastes in low-carbon concrete. They also offer a scientific basis for enhancing the mechanical and durability performance of WGRC, thereby contributing significantly to the advancement of sustainable construction materials.